2017
DOI: 10.1177/0363546517716920
|View full text |Cite
|
Sign up to set email alerts
|

Sporting Activity Is Reduced 11 Years After First-Generation Autologous Chondrocyte Implantation in the Knee Joint

Abstract: The premorbid level of sporting and recreational activities cannot be achieved 11 years after ACI-P. The MRI results determined at this time point did not conclusively correlate with long-term sporting activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
3
5
0
Order By: Relevance
“…Postoperative sports activity also showed impressive results and demonstrated significant (p < 0.05) correlation with all clinical outcome parameters. These results are in line with previous findings, which also reported significant correlations between pre-and postoperative sports activity and clinical outcome after ACI and microfracture [12,14,23]. All these results suggest that the preoperative performance level is an important indicator of the clinical outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Postoperative sports activity also showed impressive results and demonstrated significant (p < 0.05) correlation with all clinical outcome parameters. These results are in line with previous findings, which also reported significant correlations between pre-and postoperative sports activity and clinical outcome after ACI and microfracture [12,14,23]. All these results suggest that the preoperative performance level is an important indicator of the clinical outcome.…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore possible that based on the surgery result alone, an even higher postoperative sporting level could be achieved. Similar observations have already been made in earlier studies with first-generation ACI [14]. All clinical scores showed highly significant improvements for the considered patient cohort with an average of 8 years (5-14) after third-generation ACI (p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Regardless, analysis of the single treatment procedures did not result in significant correlations. Currently, evidence cannot suggest a correlation between the T2-weighted relaxation times and clinical outcomes [22]. Different scores have been introduced for qualitative assessment of the knee joint after cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in a community-level patient cohort (as opposed to professional athletes), a range of factors will affect post-operative activity level above and beyond ongoing knee problems, including family and work commitments, as well as other musculoskeletal and health concerns. Erdle et al 26 recently reported that the pre-morbid level of sporting and recreational activities cannot be achieved at a minimum of 10 years after first-generation chondrocyte implantation, though they did not inquire as to when patients altered their postoperative activity, nor the reasons behind this. The current study did not evaluate other factors that can contribute to post-operative activity, though these reasons for not attaining a higher activity profile must be acknowledged.…”
Section: Discussionmentioning
confidence: 99%